2016
DOI: 10.3892/or.2016.5325
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral-mediated overexpression of KCTD12 inhibits the proliferation of human uveal melanoma OCM-1 cells

Abstract: Human potassium channel tetramerization domain containing 12 (KCTD12, also known as Pfetin) is a member of the KCTD family which consists of 26 members. It has been reported that KCTD12 regulates agonist potency and kinetics of GABAB receptor signaling. Proteomic analysis indicates that KCTD12 may be a potential biomarker for the diagnosis and prognosis of gastrointestinal stromal tumors. However, little has been reported concerning the role of KCTD12 in the other tumor types. In the present study, we designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In addition, KCTD12 was widely reported to be downregulated in gastrointestinal stromal tumors (GISTs) and served as a powerful prognostic marker for GISTs 56 . However, few studies have focused on the role of KCTD12 in melanoma metastasis 6 . In the present study, we analyzed the correlation between KCTD12 expression levels and the clinical prognosis of SKCM patients using the GEPIA database.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, KCTD12 was widely reported to be downregulated in gastrointestinal stromal tumors (GISTs) and served as a powerful prognostic marker for GISTs 56 . However, few studies have focused on the role of KCTD12 in melanoma metastasis 6 . In the present study, we analyzed the correlation between KCTD12 expression levels and the clinical prognosis of SKCM patients using the GEPIA database.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism through which KCTD12 downregulation promoted metastasis was preliminarily investigated. KCTD12 has been reported to suppress uveal melanoma cell proliferation by prolonging G2/M to G1 phase progression 6 . Earlier reports stated that KCTD12 inhibited CRC stemness and metastasis through suppressing the ERK pathway 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another protein differentially expressed is the coagulation factor XIII (F13A1) which it was previously associated with chemotherapy response in melanoma tumors [22]. Potassium channel tetradimerization domain containing 12 (KCTD12) inhibits proliferation in uveal melanoma cells [23]. SLC9A3R1 is involved in suppressing breast cancer cells proliferation [24].…”
Section: Discussionmentioning
confidence: 99%
“…50 Luo et al demonstrated that the over expression of KCTD12 in human uveal melanoma OCM-1 cells inhibited proliferation. 51 In another report, Li et al showed that colorectal cancer cells stemness was regulated by KCTD12 via the ERK pathway. 50 Retinoic acid early-inducible protein 1-gamma, RAE-1c (4.04 fold) was also upregulated in the c-di-GMP treatment group.…”
Section: Identication Of Differentially Expressed Proteins In C-di-gmentioning
confidence: 98%